2013
DOI: 10.3109/01676830.2013.772208
|View full text |Cite
|
Sign up to set email alerts
|

Alphasphere as a Successful Ocular Implant in Primary Enucleation and Secondary Orbital Implant Exchange

Abstract: This initial report indicates that Alphasphere can be successfully used in the management of an anophthalmic socket. The advantages of the Alphasphere implant include: it does not require tissue wrapping, extraocular muscles can be directly sutured to the implant, it maintains a smooth surface to limit risk of exposure due to conjunctival breakdown, and undergoes anterior orbital fibrovascular ingrowth which optimizes prosthesis location and socket motility.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…It offered various advantages, such as eliminating the need for tissue wrapping, facilitating direct muscle suturing, reducing exposure risks, and optimizing the placement and maneuverability of prostheses. Notably, only one patient required implant removal due to a sinus infection, while another experienced slight implant shifting [163]. However, Yadav and his team presented a case of a 54-year-old diabetic patient who underwent a secondary Alphasphere implant after enucleation due to endophthalmitis.…”
Section: Poly(methylmethacrylate) (Pmma)mentioning
confidence: 99%
“…It offered various advantages, such as eliminating the need for tissue wrapping, facilitating direct muscle suturing, reducing exposure risks, and optimizing the placement and maneuverability of prostheses. Notably, only one patient required implant removal due to a sinus infection, while another experienced slight implant shifting [163]. However, Yadav and his team presented a case of a 54-year-old diabetic patient who underwent a secondary Alphasphere implant after enucleation due to endophthalmitis.…”
Section: Poly(methylmethacrylate) (Pmma)mentioning
confidence: 99%
“…Alphasphere is an FDA-approved orbital implant made of poly-HEMA (2-hydroxyethyl methacrylate). Its unique two-phase structure, which combines a porous sponge front with a nonporous gel back, enhances prosthesis placement and maneuverability while mitigating tissue integration risks [ 52 ]. In a study, Shevchenko et al demonstrated its effectiveness in managing anophthalmic sockets, offering benefits such as direct muscle suturing and reduced exposure risks.…”
Section: Oculoplastic and Orbital Surgery Devicesmentioning
confidence: 99%